The existence of Suara Waditra in the Knowledge Sharing Framework - Sjuchro, Dian Wardiana; Bakti, Iriana; Rahmat, Agus; Sjafirah, Nuryah Asri; Nurfauziah, Isni (CV. Media Digital Publikasi Indonesia, 2025)
Suara Waditra Community Radio is a community radio based in Sukasetia Village, Cisayong District, Tasikmalaya Regency. This radio has a broadcasting permit from the Minister of Communication and Information in 2018. Suara Waditra Community Radio is still continuing to broadcast both to convey information about the village and just for entertainment. The aim of this research is to find out the existence of Suara Waditra Community Radio in the community, especially in context knowledge sharing. This research is a qualitative descriptive study. Research data was collected through interviews and observations. This research shows that Suara Waditra Community Radio faces significant problems related to a lack of human resources. Radio can only broadcast a limited number and quality of programs due to these conditions, often with a focus on entertainment programming rather than educational or awareness programming. The development and success of community radio is also hampered by the lack of community participation in supporting radio operations through funding and active involvement as a broadcasting institution. In addition, this research found that Suara Waditra Community Radio still has loyal listeners, especially among the elderly and those who have not fully used modern technology, despite competition from digital media. The Village Corner program shows how community radio can help empower communities and spread local information that is not reported by mainstream media.